Portugal, 2011: the victory of the neoliberal right, the defeat of the left - Santana Pereira, J. (Portuguese Journal of Social Science, 2012)
The present article analyses the 5 June 2011, parliamentary elections in Portugal, and begins by introducing the reader to the background of the elections: the exercise of power in the 11th legislature, the economic crisis, the Bailout Agreement for Portugal, and the electoral campaign. Then the 2011 electoral results are described and compared with previous national elections. Overall, the picture displays a strong defeat of the left that paved the way for the most neoliberal government in Portuguese history. Voters also voted for stability: the right-wing parties declared they were willing to co-operate (and in fact they formed a coalition government very quickly), whereas the left-wing parties have shown on several occasions that they are unable and unwilling to co-operate.